Performance and microbial community features of tidal-flow biochar-amended constructed wetlands treating sodium dodecyl sulfate (SDS)-containing greywater. (10th April 2023) - Zhou, Yun; Ji, Bohua; Jiang, Ming; Jin, Yiyang; Chang, Junjun
Abstract: A large quantity of surfactants (e.g., sodium dodecyl sulfate (SDS)) are discharged along with greywater especially during the COVID-19 pandemic, while information on the treatment of surfactant-containing greywater using eco-friendly constructed wetlands (CWs) and the impact of surfactants on CW systems has rarely been reported. In the present study, lab-scale CWs amended with a biochar substrate and operated in tidal flow (TF) mode were used to treat SDS-containing greywater. The results showed that the biochar-amended CWs removed NH4 + -N significantly better (18.2–37.9%) than the gravel-only CWs (2.5–24.6%) but removed phosphorus (P) and COD less efficiently, and the feeding of SDS at 50 and 100 mg/L led to a notable decrease in N removal. TF not only notably improved the pollutant removal performance but also effectively eliminated SDS stress in the CWs (NH4 + -N removal of 67.1–72.1%). Mean SDS removal efficiencies of 75.3–79.3% were obtained in the CWs. TF mode altered the microbial community structure and metabolic pattern and enhanced the abundance of functional bacteria related to N and P removal in the CWs. The bacterial community shifted considerably with SDS feeding, resulting in higher species diversity and more intensive co-occurrence network relationships. TF-CWs filled with composite substrates are highly feasible and promising for the treatment of SDS-containing greywater. Graphical abstract: Image 1 Highlights: SDS-containing greywater was treated by constructed wetlands (CWs) with different setups. SDS caused a dose-response reduction in nitrogen removal in flooded CWs. Tidal flow (TF) mode notably enhanced CW treatment performance and eliminated SDS stress. SDS feeding and TF enhanced microbial diversity and regulated community structure. SDS feeding notably strengthened microbial interspecific interactions in the CWs.